Pengaruh Pertumbuhan Ekonomi dan Indeks Pembangunan Terhadap Kemisikinan di Provinsi Sumatera Utara - Aprilia, Silvi; Suheri; Sembiring, Vika Haryani Br; Tanjung, Shauma Putri Alifiyah; Ramadani, Rika; Nasution, Nabila (Ikatan Da'i Indonesia, 2025)
This study aims to analyze the effect of economic growth and development index on poverty level in the provinc of North Sumatera. The data used in this study are secondary data obtained from the Central Statistics Agency (CSA). The analysis method used in this study is Vector Autoregression (VAR) to identify the relationship between independent variables, namely economic growth and development index on poverty levels. The results of the study indicate that economic growth has a significant negative effect on poverty, whilw the development index has a significant positive effect on poverty. This study concludes that the combination of economic growth and development index can be an effective strategy to reduce poverty rates. Therefore, the government and lawmakers are expected to prioritize development that is oriented towards community welfare.